Prevalence and effects of sleep-disordered breathing on middle-aged patients with sedative-free generalized anxiety disorder: A prospective case-control study - Chen, Tien-Yu; Kung, Yen-Ying; Lai, Hsiao-Ching; Lee, Li-Ang; Jen, I-An; Chang, Hsin-An; Liu, Chia-Yu; Kuo, Terry B. J.; Yang, Cheryl C. H. (Frontiers in Psychiatry, 2023)
Objective Generalized anxiety disorder (GAD) and sleep-disordered breathing (SDB) share similar symptoms, such as poor sleep quality, irritability, and poor concentration during daily activities. This study aims to investigate the proportion of undiagnosed SDB and its impacts on anxiety severity and autonomic function in newly diagnosed, sedative-free GAD patients. Methods This prospective case-control study included newly diagnosed GAD patients and control participants with matched age, sex, and body mass index (BMI) in Taiwan. All participants completed questionnaires for sleep and mood symptoms and a resting 5-min heart rate variability (HRV) examination during enrollment. The participants also used a home sleep apnea test to detect SDB. An oxygen desaturation index (ODI) ≥5 was considered indicative of SDB. Results In total, 56 controls and 47 newly diagnosed GAD participants (mean age 55.31±12.36 years, mean BMI 23.41±3.42 kg/m2) were included. There was no significant difference in the proportion of undiagnosed SDB in the control and sedative-free GAD groups (46.43% vs 51.06%). Sedative-free GAD patients with SDB scored significantly higher on Beck Anxiety Inventory (23.83±11.54) than those without SDB (16.52±10.61) (p<0.001). Both control and sedative-free GAD groups with SDB had worse global autonomic function than the control group without SDB, as evidenced by the HRV results (p<0.05 for all). Conclusions Average age 55 years and mean BMI 23 kg/m2 patients with GAD and matched controls had an undiagnosed SDB prevalence of approximately 50%. SDB correlated with worsening anxiety severity and reduced cardiac autonomic function. Moreover, age and BMI were considered major risk factors for predicting undiagnosed SDB.